Closing the loop on water supply and sanitation: The dynamic links between population, ecosystems, and economic interactions - Jean M P De Paula; Francisco S Pinto; Amílcar Arantes; Rui C Marques (Sustainable Futures)
Water Supply and Sanitation (WSS) services face challenges as high investment costs, contextual characteristics and constraints, and conflicting interests. Increasing the access and demands evolve the focus to specific requirements, possibly diverting WSS from their core purposes and functional needs to deliver the services. Guarantee human basic needs in our interconnected and complex society has become challenging. This study proposes a comprehensive approach to expose feedback loops related to WSS effects and dependencies. Notably, a Causal Loop Diagram (CLD) shows a novelly way to qualify decision making processes and public policies associating the feedback loops relating overall goal to the sectorial needs, promoting the (re)concile of collective and individual values enrolled. Bringing the financial dependence close to WSS´s their role in health uncovers critical links to the environment and economic development, particularly the population growth, the ecosystem consequences, and the economic feedback dependence. To validate the CLD-to-WSS model, expert judgment was integrated into the modeling process, and further research can build on this knowledge, identifying evidence to support the process, bridging perceptions to quantitative results comprehensively.